Conversion of Waste Oil into Fuel Oil : - Tri Kurnia Dewi (Sriwijaya International Seminar on Energy-Environmental Science and Technology, 2014)
Research has been conducted to convert waste lubrication oil into fuel oil. This work is the second part of a bigger work entittled â€œConversion of Waste Oil into Fuel Oilâ€. The first part dealing with the production of catalyst and the effect of temperature, whilst this part studying the effect of catalyst ratio. This work was done with procedure similar with the first part of the work. Convertion of waste lubrication oil into fuel oil was done using hydrocracking process with catalyst of combination of chromium and activated natural zeolith (Cr/ZAA). Controlled variables used for this researh were the type of waste oil (lubrication oil), feed volume (40 ml), temperature (500Â°C), and hydrogen gas rate (20 ml/sec). The weight ratio of the catalyst and waste oil feed was varied at 1/8, 1/4, 1/3, 1/2, and 2/3. The parameters used to analyse the results were the amount of hydrocracking product, percentage of cracking fraction (gasoline, kerosene and solar) in the product and the heating value of the product. Analytic works were carried out with GC for cracking fraction and bomb calorimeter for heating value of the produced fuel oil. Results showed that the amount of hydrocracking product decreases with the increase of catalyst ratio. Increasing catalyst ratio increases gasoline fraction lineary, decreases kerosene and solar fractions. The heating value of the product lineary increases with catalyst ratio. Best catalyst ratio for this work was 1/8 to get maximum amount of product (13.16 ml for 40 ml feed), and 2/3 to get maximum gasoline fraction (56.70%), and highest heating value (44.92 kJ/gr).